TIMSS (Journal of Science-Innovative Research in Uzbekistan, 2024)
The Trends in International Mathematics and Science Study (TIMSS) is an influential international assessment that measures the mathematics and science achievement of students across various countries. Since its inception in 1995, TIMSS has provided critical data on the performance of students in these subjects, offering valuable insights into educational systems worldwide. This article explores the goals of TIMSS, the methodology behind the study, and the key findings over the years, highlighting the educational implications and potential strategies for improving performance in mathematics and science globally. Furthermore, the article examines how TIMSS data can be used to inform educational policy and curriculum development